Online engage-measurement in tutoring session - Siddique, Saadman Omar; Alam, M. Shafiul; Alam, Mahmud; Hasan, Nabil; Tajwar, M. M. Hasan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.